2021
DOI: 10.1038/s41467-021-24112-w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of response to PD-L1 blockade across tumor types

Abstract: Immune checkpoint inhibitors targeting the PD-1/PD-L1 axis lead to durable clinical responses in subsets of cancer patients across multiple indications, including non-small cell lung cancer (NSCLC), urothelial carcinoma (UC) and renal cell carcinoma (RCC). Herein, we complement PD-L1 immunohistochemistry (IHC) and tumor mutation burden (TMB) with RNA-seq in 366 patients to identify unifying and indication-specific molecular profiles that can predict response to checkpoint blockade across these tumor types. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(110 citation statements)
references
References 43 publications
3
107
0
Order By: Relevance
“…On the basis of results obtained in other tumors, clearly indicating that non-immune pathways could impact response to ICI therapy, an additional combination therapy that can be proposed for STS will envisage the use of drugs targeting CDKs [ 69 ]. In fact, CDK activation pathways are drivers of sarcomagenesis, but they also have an active role in limiting immune surveillance in human tumors and likely in sarcomas, as well.…”
Section: Genetic/immunological Diversity In Stss and Response To Icismentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of results obtained in other tumors, clearly indicating that non-immune pathways could impact response to ICI therapy, an additional combination therapy that can be proposed for STS will envisage the use of drugs targeting CDKs [ 69 ]. In fact, CDK activation pathways are drivers of sarcomagenesis, but they also have an active role in limiting immune surveillance in human tumors and likely in sarcomas, as well.…”
Section: Genetic/immunological Diversity In Stss and Response To Icismentioning
confidence: 99%
“…In fact, CDK activation pathways are drivers of sarcomagenesis, but they also have an active role in limiting immune surveillance in human tumors and likely in sarcomas, as well. Moreover, it has been recently reported that CDK4/6 axis is a tumor-intrinsic resistance mechanism to anti PD1 therapy in melanoma [ 70 ] and increased activity of the CDK4/6 inhibitor CDKN2A correlates with response to PD-L1 blockage in RCC and NSCLC patients [ 69 ].…”
Section: Genetic/immunological Diversity In Stss and Response To Icismentioning
confidence: 99%
“…Some targeted therapeutic agents targeting vascular endothelial growth factor (VEGF) signaling, such as sunitinib and pazopanib, have greatly improved the prognosis of ccRCC patients. Additionally, immune checkpoint inhibitor alone or combined strategies were also identified as a promising therapeutic target for those patients ( 5 , 6 ). Revealing comprehensive genomic features is of great importance for understanding ccRCC and developing new therapeutic lines for patients with ccRCC ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, lung adenocarcinoma patients with lower risk score or higher CDKN2A expression levels present more immune cells in TIME, suggesting an activated immune phenotype that results in longer overall survival. The correlation between CDKN2A expression and response to ICI treatment was also demonstrated in a recent study, highlighting the association of non-immune pathways to the outcome of ICI treatment (29). Nevertheless, further investigation is needed to explore the biological roles of CDKN2A.…”
Section: Discussionmentioning
confidence: 71%